Study on the structural and electromagnetic properties of Tm-substituted Mg-Mn ferrites by a solution combustion method - Lwin, N.; Othman, R.; Sreekantan, S.; Fauzi, M.N.A. (Elsevier, 2015)
The effect of thulium ion substitution for iron on the structural and electromagnetic properties of Mg-Mn ferrites is reported. The Mg0.9Mn0.1TmxFe1.8-xO4 ferrite compositions with x=0.0, 0.025, 0.05, and 0.075 were synthesized by a nitrate-citrate solution combustion method. Tm substitution had taken place and this was found to produce a secondary phase TmFeO3. The crystallite size of the powder calcined at 500 degrees C was in the range of 9-13 nm. Subsequently, the calcined ferrite powders were compacted and sintered at 1250 degrees C. It was found that the physical and magnetic properties had changed with Tm contents. Bulk density was found to decrease from 4.26 to 3.82 g/cm(3) with increasing Tin contents. It was also found that the saturation magnetization (M-s=38.41-23.62 emu/g) had decreased with an increase of Tm. In this study, the highest resistivity (39.84 x 10(6) Omega cm) was observed for Mg0.9Mn0.1Fe1.725Tm0.075O4. The correlation between structural and electromagnetic properties of the Tm-substituted samples is interpreted based on phase composition as well as microstructure. (C) 2015 Elsevier B.V. All rights reserved